SPS211 : Exersice physiology / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2023)
Ability to explain the concept and characteristics of agents. Ability to use the main approaches taken to developing agents.Ability to describe the key issues in designing societies of agents that can effectively corporate in order to solve problems. Ability to survey the main application areas of agent based solutions.